2022
DOI: 10.3390/ijms23158338
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanistic Understanding of RAD51 Defibrillation: A Critical Step in BRCA2-Mediated DNA Repair by Homologous Recombination

Abstract: The cytotoxic action of anticancer drugs can be potentiated by inhibiting DNA repair mechanisms. RAD51 is a crucial protein for genomic stability due to its critical role in the homologous recombination (HR) pathway. BRCA2 assists RAD51 fibrillation and defibrillation in the cytoplasm and nucleus and assists its nuclear transport. BRC4 is a peptide derived from the fourth BRC repeat of BRCA2, and it lacks the nuclear localization sequence. Here, we used BRC4 to (i) reverse RAD51 fibrillation; (ii) avoid the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 37 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…The detailed mechanism of RAD51 fibril disassembly was recently described as a multistep process, in which BRC4 erodes RAD51 fibrils from their termini through a “domino” mechanism [13] . This yields monomeric RAD51, which is the first essential step in BRCA2‐mediated homologous recombination [13] . AF2 predicted a conformational shift of RAD51 N‐terminal when it is in complex with BRC4 (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The detailed mechanism of RAD51 fibril disassembly was recently described as a multistep process, in which BRC4 erodes RAD51 fibrils from their termini through a “domino” mechanism [13] . This yields monomeric RAD51, which is the first essential step in BRCA2‐mediated homologous recombination [13] . AF2 predicted a conformational shift of RAD51 N‐terminal when it is in complex with BRC4 (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…It was recently demonstrated that BRC4 can disassemble RAD51 fibrils in the absence of DNA. [13] This study suggested that, upon DNA damage, BRCA2 (through its BRC repeats) disassembles RAD51 cytosolic fibrils, recruits monomers of RAD51, and transports them into the nucleus. [13] The oligomeric behavior of RAD51 makes it challenging to investigate this mechanism, allowing for the discovery of only scraps of indirect biochemical evidence of RAD51's interaction with the BRC repeats.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…RAD51 is a highly structurally conserved molecule in organisms ranging from Escherichia coli to higher mammals and plays an important role in maintaining genome stability [1,2]. RAD51 forms a complex with breast cancer susceptibility gene 2 (BRCA2) upon DNA damage, such as DNA double-strand breaks (DSB) for homologous recombination (HR) repair [3,4]. HR is catalyzed by RAD51 recombinase, which forms a nucleoprotein filament on resected single-stranded DNA (ssDNA) at the damage site, and mediates the pairing of homologous DNA sequences and strand invasion [5].…”
Section: Introductionmentioning
confidence: 99%